2010
DOI: 10.1590/s0074-02762010000500016
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-associated visceral leishmaniasis in patients from an endemic area in Central-west Brazil

Abstract: An increase in morbidity associated with visceral leishmaniasis (VL) in human immunodeficiency virus (HIV)/ AIDS patients has been described in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
41
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 26 publications
6
41
2
3
Order By: Relevance
“…The recurrence rate of VL in this study was significantly higher in the group of HIV/AIDS co-infected patients; it was higher than that reported by Marques et al 34 (26%) but lower than that reported by Oliveira et al 32 (56.5%). There was no significant association between the recurrence rates and the medications used including, amphotericin B deoxycholate, liposomal amphotericin B, lipid complex, and glucantime, as confirmed by the literature which has described similar efficacy between medications, although liposomal amphotericin B is associated with minor toxicities 9,18 .…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…The recurrence rate of VL in this study was significantly higher in the group of HIV/AIDS co-infected patients; it was higher than that reported by Marques et al 34 (26%) but lower than that reported by Oliveira et al 32 (56.5%). There was no significant association between the recurrence rates and the medications used including, amphotericin B deoxycholate, liposomal amphotericin B, lipid complex, and glucantime, as confirmed by the literature which has described similar efficacy between medications, although liposomal amphotericin B is associated with minor toxicities 9,18 .…”
contrasting
confidence: 77%
“…27 and Hurissa et al 28 . Our mortality rates were lower than those reported in a study conducted in Belo Horizonte (15) (17%) but higher than those reported by Oliveira et al 32 (8.7%) and Soares et al 35 (7.5%). The mortality and recurrence rates reflect the importance of the early detection and treatment of HIV in patients with VL, in order initiate appropriate treatment and prevent mortality.…”
contrasting
confidence: 75%
See 1 more Smart Citation
“…Evidence for a favorable response to therapy (clinical remission) was considered when the patient was afebrile and when physical signs as well as laboratory abnormalities significantly improved after a complete course of treatment 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Esta misma diversidad se refleja también en las dificultades que se presentan en su tratamiento, tanto en relación con el tipo de fármacos usados como en la dosificación de los mismos (Lindoso, Costa, Queiroz, & Goto, 2012). Su importancia médica es ampliamente conocida en las zonas tropicales del mundo, especialmente en su manifestación visceral, que ha causado y sigue ocasionando un número importante de muertes, especialmente cuando está asociada al virus del SIDA (Alexandrino-de-Oliveira et al, 2010). Los tipos de leishmaniosis cutáneos usualmente no causan la muerte, pero sus manifestaciones ulcerosas, no solo son estéticamente inconvenientes, sino dolorosas y proclives a infecciones secundarias bacterianas.…”
unclassified